PTH-026 Does reduction in midazolam concentration affect colonoscopy outcomes?. (23rd September 2015) - Jackson, T; Tran, S; Sharp, T; Singh, S; Lipscomb, G R
Abstract : Introduction: Following BSG recommendations in 2006, 1 we showed that replacement of 5 mg/ml with 2 mg/ml concentration of midazolam led to a decrease in the amount of midazolam used with no compromise in the quality of endoscopy.2 In December 2008 the National Patient Safety Agency issued a rapid response report on midazolam for conscious sedation.3 The recommendation was to replace all 5 mg/ml and 2 mg/ml vials of midazolam with the weaker 1 mg/ml strength. This was done in our unit in Feb 2009. We investigated the effects of this further reduction in midazolam concentration on total doses delivered during colonoscopy, adequacy of examinations and the incidence of over sedation. Methods: We reviewed colonoscopy data from 2-month periods in 2006 (midazolam 5 mg/ml), 2008 (2 mg/ml) and 2009 (1 mg/ml). Mean doses of midazolam and pethidine were recorded. Outcome measures for colonoscopy were caecal intubation rate and detection of adenomas and carcinomas. We also determined the percentage of patients with a deterioration in their comfort scores collected prospectively for 2 weeks during each data collection period. Episodes of flumazenil use are also reported. Results: Data from over 1250 cases are shown with mean±SD for drug doses. Mann–Whitney U test was used to compare drug doses between 2006 vs 2008 and 2008 vs 2009 (*p<0.0001) (Abstract 026 ). Conclusion: Reduction in midazolam concentration led to a reduction in the mean dose of midazolam given at colonoscopy without affecting the concomitant use of opiates. In addition, there were no adverse effects on colonoscopy outcomes. Although some of these finding may be attributable to better endoscopic skills, improved endoscopy equipment or closer adherence to recent guidelines, there is at least compelling evidence now that the drive towards safe sedation can be achieved without compromising quality during colonoscopic examination. We conclude that reduction in midazolam concentration to 1 mg/mL facilitates lower overall doses of sedation and subsequent improvements in patient safety while also providing adequate sedation with no detriment to procedural success.